Management and Prognosis of Interstitial Lung Disease With Lung Cancer (ILD-LC): A Real-World Cohort From Three Medical Centers in China - Xiaohong, Xie; Liqiang, Wang; Na, Li; Xinqing, Lin; Yinyin, Qin; Ming, Liu; Ming, Ouyang; Qian, Han; Qun, Luo; Shiyue, Li; Chunyan, Li; Xiaoqian, Wang; et al. (Frontiers in Molecular Biosciences, 2021)
Background and Objective: Interstitial lung disease with lung cancer (ILD-LC) is rare and its management has not been fully described. This study aimed to investigate the management and prognosis of ILD-LC patients in China. Methods: The present analysis is a retrospective real-world cohort study. Clinical data of ILD-LC patients were obtained from 3 hospitals in China. The overall survival (OS) of patients was analyzed. Univariate and multivariate regression analyses were performed. Results: 184 ILD-LC patients included were biased toward male (85.3%), smokers (75.5%), idiopathic pulmonary fibrosis (IPF) (58.2%) patients with comorbidities (67.9%) and ECOG-PS score of 1 (65.2%). Most patients were advanced peripheral non-small cell lung cancer. The initial anti-cancer regimen for ILD-LC is mainly chemotherapy, and patients with early-stage LC prefer surgery. In the anti-cancer cohort, the number of ILD-LC patients who underwent the 2nd and 3rd or more anti-cancer regimens were 78 (55.7%) and 32 (22.8%), respectively. In the non-anticancer cohort, the median OS was 3.5 months. In the early-stage cohort, the median OS was 14.2 months in the systematic therapy group; however, the median OS was not reached in the surgery group. In the advanced-stage cohort with systematic therapy, the median OS was 7.2 months. Interstitial pneumonia (IIP) and anti-angiogenesis were associated with OS in the univariate analysis, whereas anti-angiogenesis was an independent protective factor for advanced LC with ILD. Conclusion: Patients with ILD-LC have very poor prognosis. Appropriate anti-tumor treatment can prolong the survival time of patients who can tolerate it. Targeted therapy and immunotherapy are alternative treatments for LC patients with mild ILD. For ILD patients with advanced LC, antiangiogenic regimens significantly improve the prognosis of the disease.